If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-5x + -10) = 385 Reorder the terms: -7(-10 + -5x) = 385 (-10 * -7 + -5x * -7) = 385 (70 + 35x) = 385 Solving 70 + 35x = 385 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + 35x = 385 + -70 Combine like terms: 70 + -70 = 0 0 + 35x = 385 + -70 35x = 385 + -70 Combine like terms: 385 + -70 = 315 35x = 315 Divide each side by '35'. x = 9 Simplifying x = 9
| -2x+7=9 | | 11x-2=10x | | 2x+2x+30=3x+110 | | -(w+3)=-4x+10 | | 30x+9=11 | | 6x+60=90 | | (33.333)9cubed= | | 3b+16a-9n= | | -8x+5=-75 | | x^2-16x+89=0 | | 18x+7=29 | | (2w-3)(6-w)=0 | | (3x-5)=0 | | N+.5n=63 | | 0.7x+0.5=0.9x-0.7 | | 8(x+3)=4x+5 | | 3(y+7)=2(y+8) | | 6x+4=32 | | 2x-10-8=24-16-8x | | .143(49-7y)=14 | | -5(2-5x)+(-8x-2)=-4x-8x | | 6b=348 | | 15x/7=11/7 | | 3m-9x-1=24 | | 5-(.5)g=12 | | 5(4x-7)+13x-20=8(x+10)-15x+65 | | 15x/7=0 | | -[8z-(18z+3)]=3+(9z+10) | | 11x+2=10x+4 | | 92=2h | | X*1+2*0.6=2+X*0.9 | | 2c^2-c-6= |